Electrodes for multifocal electroretinography (mfERG): a comparison of four electrodes types - Norhani Mohidin,; Maurice K.H. Yap,; Robert J. Jacobs, (Universiti Kebangsaan Malaysia, 2014)
The purpose of this study was to compare the performance of four different electrode types in detecting the multifocal electroretinogram (mfERG) using the visual evoked response imaging system (VERIS). Multifocal ERG of 30 healthy subjects aged 17-50 years was recorded. Four different types of electrodes were used (JET contact lens, gold foil, DTL thread and c-glide carbon fiber electrodes) and the trough to peak amplitude response densities of the first order kernels (which approximated to the a and b wave of the full field electroretinogram) were compared. The JET contact lens electrode produced the highest amplitude response which was significantly different from the gold foil, DTL thread and the c-glide electrodes, but there was no significant difference between the gold foil and DTL or between DTL and the c-glide electrodes. In conclusion, contact lens electrode produced the highest response density followed by the gold foil and the DTL thread. There was no significant difference in amplitude response between the gold foil and DTL thread, therefore these two electrodes provide for viable alternatives for recording mfERG especially when there are concerns that contact lens electrode may be uncomfortable for recording periods that may take a long time.